2018
DOI: 10.1007/978-3-319-99417-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Sources of Hydrocarbon Compounds in Sediments from Obhur Lagoon: Red Sea Coast of Saudi Arabia

Abstract: Surface sediment samples from Obhur Lagoon on the Red Sea coast of Saudi Arabia were collected and analyzed to determine the levels, distribution and sources of hydrocarbon compounds. The sediments were collected using a Van Veen grab sampler, dried, extracted with a mixture of dichloromethane/methanol, and analyzed by gas chromatography-mass spectrometry. The major hydrocarbons of these lipid extracts included n-alkanes (6-645 ng g −1 ), methyl n-alkanoates (1-311 ng g −1 ), hopanes (3-219 ng g −1 ), steranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
0
0
0
Order By: Relevance
“…The TEOM levels indicated that lipid compounds were present in considerable amounts, as compared to petroliferous contaminants reported recently (Rushdi et al, 2019;. They included n-alkanes, fatty acid methyl esters, n-alkanols, sterols, biomarkers (mainly hopanes and steranes), plasticizers, and an unresolved complex mixture (UCM) of highly branched and cyclic hydrocarbons.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The TEOM levels indicated that lipid compounds were present in considerable amounts, as compared to petroliferous contaminants reported recently (Rushdi et al, 2019;. They included n-alkanes, fatty acid methyl esters, n-alkanols, sterols, biomarkers (mainly hopanes and steranes), plasticizers, and an unresolved complex mixture (UCM) of highly branched and cyclic hydrocarbons.…”
Section: Resultsmentioning
confidence: 85%
“…Thus, these activities affect the natural habitats of the lagoon and the sedimentary OM content and distribution. The main recent studies have focused on organic contaminants (Alansari, 2019;Ibrahim and Al-Farawati, 2023;Rasiq et al, 2018;Rushdi et al, 2019;Turki and Mudarris 2008), but no study has investigated the types and sources of natural OM input in the lagoon.…”
Section: Introductionmentioning
confidence: 99%
“…The lagoon is a vital habitat for various bird species and aquatic life. It is known for its picturesque landscapes, with extensive seagrass beds and mangroves that provide crucial breeding and forging grounds for a multitude of bird species, including flamingos and herons [50]. The lagoon serves as a refuge for marine life, supporting an array of fish species and diverse wildlife, making it a site of great environmental and recreational value to the Kingdom of Saudi Arabia.…”
Section: Study Areasmentioning
confidence: 99%
“…In Saudi Arabia, the coastal development of the Red Sea is part of the Saudi Giga-Project (The Red Sea Project, Vision 2030); however, such activities might disrupt the ecosystems and introduce the pollution to marine life [48]. Previous studies have shown that coastal sediments from Obhur lagoon north of Jeddah city in the Red Sea are contaminated with diverse groups of hydrocarbons from petroleum products and plasticizers from littering [49]. However, there is no information about the characteristics, sources, and levels of sedimentary organic matter in other lagoons along the Red Sea coast of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%